2019
DOI: 10.1111/1744-9987.12939
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange Therapy to Reduce Mortality in Japanese Patients With Diffuse Alveolar Hemorrhage and Microscopic Polyangiitis

Abstract: Diffuse alveolar hemorrhage (DAH) is well known as a serious complication of microscopic polyangiitis (MPA). We examined the effectiveness of plasma exchange (PLEX) therapy to reduce mortality in Japanese DAH patients with MPA. This retrospective, double‐center, observational cohort study included 20 DAH patients with MPA who were admitted to Juntendo University Hospital or Juntendo Koto Geriatric Medical Center between April 1998 and March 2018. The primary outcome was non–disease‐specific mortality. The 1‐ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…With regards to BP methods, particularly PE, there have been some reports of its use in IIM. PE has demonstrated a 60%-100% improvement rate in individuals with acute PM/DM-ILD unresponsive to conventional immunosuppressants [5,23], with higher concentrations of cytokines such as IL-1, IL-6, IL-8, IL-10, IL-12p70, IL-18, and sCD163 observed in these immunosuppressiveresistant patients. In conclusion, PE may be an effective salvage therapy for rapidly progressing anti-MDA5 antibody-positive DM/CADM-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to BP methods, particularly PE, there have been some reports of its use in IIM. PE has demonstrated a 60%-100% improvement rate in individuals with acute PM/DM-ILD unresponsive to conventional immunosuppressants [5,23], with higher concentrations of cytokines such as IL-1, IL-6, IL-8, IL-10, IL-12p70, IL-18, and sCD163 observed in these immunosuppressiveresistant patients. In conclusion, PE may be an effective salvage therapy for rapidly progressing anti-MDA5 antibody-positive DM/CADM-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of PE for treating DAH in patients with MPA is unclear [10]. We have previously performed a retrospective study showing that PE is effective for treating DAH in patients with MPA [11]. The largest clinical trial to date, PEXIVAS study which was conducted to clarify the safety and effectiveness of PE in patients with AAV [12] did not show that PE was effective [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic plasma exchange (TPE) removes ICs, antibodies, and cytokines, and has been used as an adjunct therapy in patients who do not respond to high-dose GC and CTX therapy. The 1-year survival rate of DAH patients treated with TPE is higher than that of patients treated with GC pulse therapy, whether combined with immunosuppressive agents or not [11] . However, few studies have reported that TPE treatment increases mortality [12] …”
mentioning
confidence: 99%
“…The 1-year survival rate of DAH patients treated with TPE is higher than that of patients treated with GC pulse therapy, whether combined with immunosuppressive agents or not. [11] However, few studies have reported that TPE treatment increases mortality. [12] Recombinant hereditary factor VIIa (FVIIa) has a good hemostatic effect in patients with life-threatening intractable hemorrhage.…”
mentioning
confidence: 99%
See 1 more Smart Citation